The Effect Of Using Problem Based-Learning Model Assisted By Education Games On Motivation And Critical Thingking Skill - Risnandani, Epi; Pribadi , Benny Agus; Roesminingsih , Erny (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
This study aims to determine the effect of using the problem based-learning model assisted by education games on the motivation and critical thinking skills of the mathematics subject of grade IV students of SDN 1 Krebet. The method in this study is a quantitative method with a nonequivalent control group design. Sampling is called purposive sampling and class IVA is obtained as the experimental class and IVB as the control. Data collection techniques through questionnaire methods and test methods with t-test hypothesis test analysis techniques. The results of this study indicate that the Problem Based Learning (PBL) model assisted by education games learning media has a significant effect on motivation in grade IV elementary school students. The Problem Based Learning (PBL) model assisted by education games learning media has a significant effect on critical thinking skills in grade IV elementary school students.